2018
DOI: 10.1139/cjss-2017-0152
|View full text |Cite
|
Sign up to set email alerts
|

Influence of long-term feedlot manure and inorganic fertilizer application on selected metal and trace elements in a clay loam soil

Abstract: Long-term application of feedlot manure and inorganic fertilizer to cropland may increase metals and trace elements in soils, and negatively impact agricultural land use. We sampled a surface clay loam soil at Lethbridge in southern Alberta after 16 annual applications (2014) of feedlot manure or inorganic fertilizer, as well as an unamended control. The manure treatments were stockpiled (SM) or composted (CM) feedlot manure with barley straw (ST) or wood-chips (WD), and were applied at 13, 39, and 77 Mg ha −1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…of continuous annual manure application. This Sparks (1996) could be attributed to the fact that the amount of Co applied over the years was probably low compared to the natural content of Co in these soils (Benke et al 2008, Miller et al 2018. Different results were found by Tlustoš et al (2016), who reported that long-term farmyard manure application did not significantly change the pseudo-total and potentially mobilizable element contents.…”
Section: Concentration Of Heavy Metals In Soil and Manure Samplesmentioning
confidence: 91%
See 1 more Smart Citation
“…of continuous annual manure application. This Sparks (1996) could be attributed to the fact that the amount of Co applied over the years was probably low compared to the natural content of Co in these soils (Benke et al 2008, Miller et al 2018. Different results were found by Tlustoš et al (2016), who reported that long-term farmyard manure application did not significantly change the pseudo-total and potentially mobilizable element contents.…”
Section: Concentration Of Heavy Metals In Soil and Manure Samplesmentioning
confidence: 91%
“…The total Cu content in manure reported in previous studies varied from 6.7 to 71.1 mg/kg. For total Zn, values ranged from 63 to 332.6 mg/kg (Nicholson et al 1999, Sager 2007, Benke et al 2008, Miller et al 2018. The main source of trace elements is the mineral core used for livestock feed which conditions the trace element content in manure (Miller et al 1991).…”
Section: Concentration Of Heavy Metals In Soil and Manure Samplesmentioning
confidence: 99%
“…Previous studies have shown that PRs are the primary source of trace elements (TEs) incorporated into mineral fertilizer, such as V, Cr, As, Se, Mo, Cd, and U. Accumulation of some of these elements has been observed in agricultural soils and can be highly variable based on fertilizer utilization and soil chemical properties. , Several studies have investigated the Sr isotope ratio ( 87 Sr/ 86 Sr) in PRs, and one study has shown the similarity between the 87 Sr/ 86 Sr ratio of PRs and mineral fertilizers originating from the same geographical region . Additionally, a few studies have characterized and applied the Sr isotope ratio of fertilizer as a tracer for delineating their environmental impact. ,− However, these studies have investigated the occurrence of TEs and the utility of Sr isotopes only in specific case studies.…”
Section: Introductionmentioning
confidence: 99%